prev next
 File: TortureTests/Size/100.html Author: Robert Miner Description: Mid-sized stress test containing 100 separate equations. Sample Rendering: N/A

x 0 + 0 = α x 1 + 1 = β x 2 + 2 = γ x 3 + 3 = δ x 4 + 4 = α x 5 + 5 = β x 6 + 6 = γ x 7 + 7 = δ x 8 + 8 = α x 9 + 9 = β x 10 + 10 = γ x 11 + 11 = δ x 12 + 12 = α x 13 + 13 = β x 14 + 14 = γ x 15 + 15 = δ x 16 + 16 = α x 17 + 17 = β x 18 + 18 = γ x 19 + 19 = δ x 20 + 20 = α x 21 + 21 = β x 22 + 22 = γ x 23 + 23 = δ x 24 + 24 = α x 25 + 25 = β x 26 + 26 = γ x 27 + 27 = δ x 28 + 28 = α x 29 + 29 = β x 30 + 30 = γ x 31 + 31 = δ x 32 + 32 = α x 33 + 33 = β x 34 + 34 = γ x 35 + 35 = δ x 36 + 36 = α x 37 + 37 = β x 38 + 38 = γ x 39 + 39 = δ x 40 + 40 = α x 41 + 41 = β x 42 + 42 = γ x 43 + 43 = δ x 44 + 44 = α x 45 + 45 = β x 46 + 46 = γ x 47 + 47 = δ x 48 + 48 = α x 49 + 49 = β x 50 + 50 = γ x 51 + 51 = δ x 52 + 52 = α x 53 + 53 = β x 54 + 54 = γ x 55 + 55 = δ x 56 + 56 = α x 57 + 57 = β x 58 + 58 = γ x 59 + 59 = δ x 60 + 60 = α x 61 + 61 = β x 62 + 62 = γ x 63 + 63 = δ x 64 + 64 = α x 65 + 65 = β x 66 + 66 = γ x 67 + 67 = δ x 68 + 68 = α x 69 + 69 = β x 70 + 70 = γ x 71 + 71 = δ x 72 + 72 = α x 73 + 73 = β x 74 + 74 = γ x 75 + 75 = δ x 76 + 76 = α x 77 + 77 = β x 78 + 78 = γ x 79 + 79 = δ x 80 + 80 = α x 81 + 81 = β x 82 + 82 = γ x 83 + 83 = δ x 84 + 84 = α x 85 + 85 = β x 86 + 86 = γ x 87 + 87 = δ x 88 + 88 = α x 89 + 89 = β x 90 + 90 = γ x 91 + 91 = δ x 92 + 92 = α x 93 + 93 = β x 94 + 94 = γ x 95 + 95 = δ x 96 + 96 = α x 97 + 97 = β x 98 + 98 = γ x 99 + 99 = δ x 100 + 100 = α

Source Code:

```    <math>
<msup>
<mi>x</mi>
<mn>0</mn>
</msup>
<mo>+</mo>
<mn>0</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>1</mn>
</msup>
<mo>+</mo>
<mn>1</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>2</mn>
</msup>
<mo>+</mo>
<mn>2</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>3</mn>
</msup>
<mo>+</mo>
<mn>3</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>4</mn>
</msup>
<mo>+</mo>
<mn>4</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>5</mn>
</msup>
<mo>+</mo>
<mn>5</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>6</mn>
</msup>
<mo>+</mo>
<mn>6</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>7</mn>
</msup>
<mo>+</mo>
<mn>7</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>8</mn>
</msup>
<mo>+</mo>
<mn>8</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>9</mn>
</msup>
<mo>+</mo>
<mn>9</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>10</mn>
</msup>
<mo>+</mo>
<mn>10</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>11</mn>
</msup>
<mo>+</mo>
<mn>11</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>12</mn>
</msup>
<mo>+</mo>
<mn>12</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>13</mn>
</msup>
<mo>+</mo>
<mn>13</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>14</mn>
</msup>
<mo>+</mo>
<mn>14</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>15</mn>
</msup>
<mo>+</mo>
<mn>15</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>16</mn>
</msup>
<mo>+</mo>
<mn>16</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>17</mn>
</msup>
<mo>+</mo>
<mn>17</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>18</mn>
</msup>
<mo>+</mo>
<mn>18</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>19</mn>
</msup>
<mo>+</mo>
<mn>19</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>20</mn>
</msup>
<mo>+</mo>
<mn>20</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>21</mn>
</msup>
<mo>+</mo>
<mn>21</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>22</mn>
</msup>
<mo>+</mo>
<mn>22</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>23</mn>
</msup>
<mo>+</mo>
<mn>23</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>24</mn>
</msup>
<mo>+</mo>
<mn>24</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>25</mn>
</msup>
<mo>+</mo>
<mn>25</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>26</mn>
</msup>
<mo>+</mo>
<mn>26</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>27</mn>
</msup>
<mo>+</mo>
<mn>27</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>28</mn>
</msup>
<mo>+</mo>
<mn>28</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>29</mn>
</msup>
<mo>+</mo>
<mn>29</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>30</mn>
</msup>
<mo>+</mo>
<mn>30</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>31</mn>
</msup>
<mo>+</mo>
<mn>31</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>32</mn>
</msup>
<mo>+</mo>
<mn>32</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>33</mn>
</msup>
<mo>+</mo>
<mn>33</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>34</mn>
</msup>
<mo>+</mo>
<mn>34</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>35</mn>
</msup>
<mo>+</mo>
<mn>35</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>36</mn>
</msup>
<mo>+</mo>
<mn>36</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>37</mn>
</msup>
<mo>+</mo>
<mn>37</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>38</mn>
</msup>
<mo>+</mo>
<mn>38</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>39</mn>
</msup>
<mo>+</mo>
<mn>39</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>40</mn>
</msup>
<mo>+</mo>
<mn>40</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>41</mn>
</msup>
<mo>+</mo>
<mn>41</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>42</mn>
</msup>
<mo>+</mo>
<mn>42</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>43</mn>
</msup>
<mo>+</mo>
<mn>43</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>44</mn>
</msup>
<mo>+</mo>
<mn>44</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>45</mn>
</msup>
<mo>+</mo>
<mn>45</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>46</mn>
</msup>
<mo>+</mo>
<mn>46</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>47</mn>
</msup>
<mo>+</mo>
<mn>47</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>48</mn>
</msup>
<mo>+</mo>
<mn>48</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>49</mn>
</msup>
<mo>+</mo>
<mn>49</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>50</mn>
</msup>
<mo>+</mo>
<mn>50</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>51</mn>
</msup>
<mo>+</mo>
<mn>51</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>52</mn>
</msup>
<mo>+</mo>
<mn>52</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>53</mn>
</msup>
<mo>+</mo>
<mn>53</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>54</mn>
</msup>
<mo>+</mo>
<mn>54</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>55</mn>
</msup>
<mo>+</mo>
<mn>55</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>56</mn>
</msup>
<mo>+</mo>
<mn>56</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>57</mn>
</msup>
<mo>+</mo>
<mn>57</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>58</mn>
</msup>
<mo>+</mo>
<mn>58</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>59</mn>
</msup>
<mo>+</mo>
<mn>59</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>60</mn>
</msup>
<mo>+</mo>
<mn>60</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>61</mn>
</msup>
<mo>+</mo>
<mn>61</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>62</mn>
</msup>
<mo>+</mo>
<mn>62</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>63</mn>
</msup>
<mo>+</mo>
<mn>63</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>64</mn>
</msup>
<mo>+</mo>
<mn>64</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>65</mn>
</msup>
<mo>+</mo>
<mn>65</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>66</mn>
</msup>
<mo>+</mo>
<mn>66</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>67</mn>
</msup>
<mo>+</mo>
<mn>67</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>68</mn>
</msup>
<mo>+</mo>
<mn>68</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>69</mn>
</msup>
<mo>+</mo>
<mn>69</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>70</mn>
</msup>
<mo>+</mo>
<mn>70</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>71</mn>
</msup>
<mo>+</mo>
<mn>71</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>72</mn>
</msup>
<mo>+</mo>
<mn>72</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>73</mn>
</msup>
<mo>+</mo>
<mn>73</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>74</mn>
</msup>
<mo>+</mo>
<mn>74</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>75</mn>
</msup>
<mo>+</mo>
<mn>75</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>76</mn>
</msup>
<mo>+</mo>
<mn>76</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>77</mn>
</msup>
<mo>+</mo>
<mn>77</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>78</mn>
</msup>
<mo>+</mo>
<mn>78</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>79</mn>
</msup>
<mo>+</mo>
<mn>79</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>80</mn>
</msup>
<mo>+</mo>
<mn>80</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>81</mn>
</msup>
<mo>+</mo>
<mn>81</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>82</mn>
</msup>
<mo>+</mo>
<mn>82</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>83</mn>
</msup>
<mo>+</mo>
<mn>83</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>84</mn>
</msup>
<mo>+</mo>
<mn>84</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>85</mn>
</msup>
<mo>+</mo>
<mn>85</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>86</mn>
</msup>
<mo>+</mo>
<mn>86</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>87</mn>
</msup>
<mo>+</mo>
<mn>87</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>88</mn>
</msup>
<mo>+</mo>
<mn>88</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>89</mn>
</msup>
<mo>+</mo>
<mn>89</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>90</mn>
</msup>
<mo>+</mo>
<mn>90</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>91</mn>
</msup>
<mo>+</mo>
<mn>91</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>92</mn>
</msup>
<mo>+</mo>
<mn>92</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>93</mn>
</msup>
<mo>+</mo>
<mn>93</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>94</mn>
</msup>
<mo>+</mo>
<mn>94</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>95</mn>
</msup>
<mo>+</mo>
<mn>95</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>96</mn>
</msup>
<mo>+</mo>
<mn>96</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>97</mn>
</msup>
<mo>+</mo>
<mn>97</mn>
<mo>=</mo>
<mi>&beta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>98</mn>
</msup>
<mo>+</mo>
<mn>98</mn>
<mo>=</mo>
<mi>&gamma;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>99</mn>
</msup>
<mo>+</mo>
<mn>99</mn>
<mo>=</mo>
<mi>&delta;</mi>
</math>
<span>. Consider the equation</span>
<math>
<msup>
<mi>x</mi>
<mn>100</mn>
</msup>
<mo>+</mo>
<mn>100</mn>
<mo>=</mo>
<mi>&alpha;</mi>
</math>
<span>.</span>
```